Applying the NIMSAD Framework to Evaluating IA Education Projects - Armstrong, Helen; Jayaratna, Nimal (Not stated, 2005)
This paper applies the NIMSAD framework to the evaluation of IA education projects. The framework considers elements relating to the education process, the education practice, and the educators as project teams. It is proposed that the evaluation of the above elements takes place at a minimum of three time periods using the criteria of efficacy, efficiency and effectiveness. The framework recognizes the importance of the human element and provides a holistic process to evaluating IA education projects. The generic nature of the framework allows its adaptation to other curriculum development, IT and security related projects and research.